Perlindungan Hukum bagi Penghadap Penyandang Disabilitas Tuna Netra dalam Proses Pembuatan Akta Otentik - Mustika, Dwi (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study aims to analyze the limitations of legal actions and legal protection for persons with visual impairments in the process of making a deed. The method used in this study is normative juridical with statutory and conceptual approaches. The results of the study show that the limitation of legal action can be seen in the provisions of a notary which requires representatives for persons with visual impairments in the process of making a deed. People with visual impairments have limitations in knowing the contents of the deed they made because they have not been facilitated with braille. Legal protection for persons with visual impairments in the process of making a deed has not been regulated in laws and regulations. Legal protection for persons with disabilities in the process of making a deed is very necessary to avoid bad faith on the part of the parties concerned. Abstrak: kajian ini bertujuan menganalisi